Work productivity (absenteeism and presenteeism) in persons with common mental disorders: An observational study from South India - Manjunatha B. Kondapura; Narayana Manjunatha; Anil Kumar M. Nagaraj; Samir K. Praharaj; Channaveeraachari N. Kumar; Suresh B. Math; Girish N. Rao (Indian Journal of Psychiatry)
Background: The greatest contributor to the economic impact of common mental disorders (CMDs) is said to be the loss of work productivity. There is a paucity of studies from India that looks at the impact of CMDs on the productivity of work, which costs both patient and society significantly. Aim: To assess and compare work productivity by evaluating both absolute and relative presenteeism and absenteeism, in persons with CMDs. Materials and Methods: This was a cross-sectional observational study on 220 subjects (110, 58, and 52 patients with depressive disorder, anxiety disorders, and somatoform disorders, respectively), recruited through purposive sampling. We evaluated work productivity using the World Health Organization Health and Work Performance Questionnaire. Results: Absolute absenteeism was significantly different before and after treatment for CMDs as a group but not for individual disorders. Relative absenteeism, absolute presenteeism, and relative presenteeism were all significantly different before and after treatment among both CMDs as a group and also among individual disorders. Both presenteeism and absenteeism (absolute as well as relative) did not differ significantly across the diagnostic groups. Work productivity has been linearly associated with illness severity and disability. Conclusion: CMDs are associated with a significant loss of work productivity. Presenteeism is costlier than absenteeism in affecting work productivity. Loss of work productivity appears to be transdiagnostic across all CMDs. Also, the severity of loss of work productivity is associated linearly with the severity of illness and disability.